The Need to Belong: An Exploration of Belonging Among Urban Middle School Students. Issue 1 (2nd January 2019) - Stickl Haugen, Jaimie; Wachter Morris, Carrie; Wester, Kelly
Abstract : This study explored the subjective perspectives of the affective, behavioral, and familial dimensions of belonging among urban middle school students through the use of Q methodology. Three viewpoints emerged representing distinct viewpoints of belonging, including students who identified belonging in relation to academics and academic behaviors, those who desired affective connection with others, and those who equated belonging with cultural respect and adult support. Findings support the complex and multidimensional nature of belonging with important implications for mental health and school counselors who have the opportunity to foster adolescents' sense of belonging.